Review of Sewage Sludge Composting Technologies - Khalid, Suleiman Ibrahim; Makádi, Marianna; Abdulkadir, Mustapha; Szegi, Tamás (Journal of Central European Green Innovation, 2025)
The recycling of wastewater residues plays a crucial role in the circular economy, a key focus of the EU’s 2030 Green Deal. A byproduct of wastewater treatment, sewage sludge, can serve as a sustainable resource for plant nutrition through the application of various composting technologies. Composting helps mitigate pollution by converting organic waste, such as sewage sludge, into compost with the aid of microorganisms. The resulting compost enhances soil quality and health. Several composting approaches—windrow composting, aerated static windrow composting, vermicomposting, and in-vessel composting—each have unique advantages and disadvantages in terms of environmental impact, efficiency, and sustainability. This paper provides an overview of composting methodologies and explores advanced composting technologies for optimizing sewage sludge composting. Aerobic composting is the most widely used method due to its efficiency and ability to eliminate pathogens; however, concerns remain regarding greenhouse gas emissions and nutrient losses. To address these challenges, co-composting, vermicomposting, and two-phase composting have been developed to enhance compost quality and shorten processing times. Despite these advancements, land restrictions, complex technologies, and high costs remain significant limitations. This study emphasizes the importance of microbial dynamics, pathogen elimination, and compost maturation during key composting stages, from the mesophilic to the thermophilic phase, in order to produce stable, nutrient-rich compost. While composting technologies align with sustainability goals, further research is needed to improve efficiency, reduce emissions, and assess potential economic impacts. This review highlights the critical role of composting in achieving waste management and environmental sustainability objectives.